2017
DOI: 10.1111/tgis.12267
|View full text |Cite
|
Sign up to set email alerts
|

A spatial parallel heuristic approach for solving very large‐scale vehicle routing problems

Abstract: The vehicle routing problem (VRP) is one of the most prominent problems in spatial optimization because of its broad applications in both the public and private sectors. This article presents a novel spatial parallel heuristic approach for solving large-scale VRPs with capacity constraints. A spatial partitioning strategy is devised to divide a region of interest into a set of small spatial cells to allow the use of a parallel local search with a spatial neighbor reduction strategy. An additional local search … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 49 publications
(70 reference statements)
1
6
0
Order By: Relevance
“…By consulting the latest relevant research literature, we found that they only contain one or part of the above constraints, rather than all. Tu [2] proposed a novel spatial parallel optimization approach integrating spatial partitioning, local search, and parallel, effectively solving the very large-scale VRP of thousands of customers within half an hour. However, this method only restricts vehicle capacity.…”
Section: ) Heterogeneous Fixed Fleetmentioning
confidence: 99%
“…By consulting the latest relevant research literature, we found that they only contain one or part of the above constraints, rather than all. Tu [2] proposed a novel spatial parallel optimization approach integrating spatial partitioning, local search, and parallel, effectively solving the very large-scale VRP of thousands of customers within half an hour. However, this method only restricts vehicle capacity.…”
Section: ) Heterogeneous Fixed Fleetmentioning
confidence: 99%
“…The TSP route should eventually return to the departure point. When more than one vehicle is considered, VRP is used to find the optimal routes traversing a set of locations for a fleet of vehicles [7,8]. Different from TSP, in VRP, multiple vehicles depart from depots or warehouses and cooperate to deliver or pick-up goods [36].…”
Section: Route Optimizationmentioning
confidence: 99%
“…Different from TSP, in VRP, multiple vehicles depart from depots or warehouses and cooperate to deliver or pick-up goods [36]. All three types of models have been widely applied in many smart city applications, such as pedestrian navigation in complex urban environment [37], tourist route recommendation [38], taxicab operations [39], urban logistics [7,8], etc.…”
Section: Route Optimizationmentioning
confidence: 99%
See 2 more Smart Citations